2008
DOI: 10.1007/s11274-008-9659-9
|View full text |Cite
|
Sign up to set email alerts
|

Microbial transformation of phytosterols mixture from rice bran oil unsaponifiable matter by selected bacteria

Abstract: Rice bran sample (12 Kg) was extracted and rice bran oil (RBO % 76.8 g) was saponified. The resulted unsaponifiable matter of RBO (RBO unsap) was qualitatively and quantitatively estimated using different chromatographic analyses. RBO, produced 9.65% unsaponifiable matter with the following contents, cholesterol, 6.75%; stigmasterol, 3.4%; b. sitosterol, 10.23% and campesterol, 4.2%, in addition to unknown phytosterols, hydrocarbons and waxes. Microbial transformation process started by screening of 35 bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…The incubation time is critical for steroid biotransformation. Maximum production of BOL in our study was achieved at 36 h (42.4%), on extending the fermentation process to 60 h, a remarkable reduction in BOL% was noticed, The same results were reported by others [7] , [29] . The results of these experiments indicated that AD and ADD production depended strongly on biotransformation time and substrate concentration [30] .…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The incubation time is critical for steroid biotransformation. Maximum production of BOL in our study was achieved at 36 h (42.4%), on extending the fermentation process to 60 h, a remarkable reduction in BOL% was noticed, The same results were reported by others [7] , [29] . The results of these experiments indicated that AD and ADD production depended strongly on biotransformation time and substrate concentration [30] .…”
Section: Resultssupporting
confidence: 92%
“…Optimum pH 8 was also reported by Goswami et al [31] for production of AD (D) from 17-ketosteroids by Arthrobacter . In addition, optimal pH between 6 and 8 for steroid biotransformation had referred by several reports as Sallam et al [7] and Zhang et al [25] ; they reported optimal pH at 7. Abd-Elsalam et al [30] reported optimum pH 6.5 for production of androstenedione (AD) and androstadienedione (ADD) from sunflower oil sterols by Fusarium solani .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Several researchers have reported their work in developing a microbial biotransformation process with high yield of AD with wide industrial applications [9][10][11]. Therefore, it was important to understand the factors affecting the actual biotransformation process.…”
Section: Substrate Solubilitymentioning
confidence: 99%